Defining Meaningful Functional Improvement on the Visual Analog Scale for Satisfaction at 2-years After Hip Arthroscopy for Femoroacetabular Impingement Syndrome. Issue 7 (31st July 2020) - Beck, Edward; Nwachukwu, Benedict; Mehta, Nabil; Jan, Kyleen; Okoroha, Kelechi; Drager, Justin; Nho, Shane; Rasio, Jonathan
Objectives: Patient satisfaction is being increasingly reported in orthopaedic sports medicine and the field of hip preservation surgery. The Visual Analog Scale (VAS) for Satisfaction is most commonly utilized. Currently there is limited understanding for what should be considered as clinically important improvement on the VAS Satisfaction. The purpose of this study is to 1) define Substantial Clinical Benefit (SCB), Patient Acceptable Symptomatic State (PASS), and Minimal Clinically Important Difference (MCID) for the VAS Satisfaction in patients undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS), and 2) identify preoperative predictors of achieving each outcome end-point. Methods: Data from consecutive patients who underwent primary hip arthroscopy between November 2014 and January 2017 were collected and analyzed. Baseline data and postoperative patient-reported outcome (PRO) scores were recorded at 2-years postoperatively. In order to quantify clinical significance of outcome achievement on the VAS Satisfaction we calculated MCID, PASS and SCB for this outcome measure. A multivariate logistic regression analysis was used to identify preoperative predictors of achieving SCB, PASS, and MCID satisfaction. Results: A total of 335 patients were included in the final analysis, with an average age and body mass index (BMI) of 32.8(SD+12.4) years and 25.2(SD+5.3) respectively. The values on the VAS satisfaction were identified to represent MCID, PASS and SCB respectively: 12.3, 80.9 and 89.7. The rates of achieving clinically significant improvement on the VAS Satisfaction was 97.1%, 68.1% and 56.9% for MCID, PASS and SCB respectively. A larger preoperative alpha angle was predictive for achieving SCB (OR:1.076; p =0.046), while lower BMI (OR:0.955; p =0.047) and larger preoperative alpha angle (OR:1.12; p-value=0.025) were predictors for achieving PASS. Conclusions: This study identifies scores on the VAS Satisfaction that can be used to define clinically significant outcome after arthroscopic treatment of FAIS. Specifically, an improvement of 12.3 points is a clinically important improvement in satisfaction, while an absolute score above 89.7 represents the upper threshold of Satisfaction performance. Almost all patients (97.1%) demonstrated a clinically important improvement in satisfaction. Additionally, there are both modifiable and non-modifiable factors that predict achieving a clinically significant level of post-operative satisfaction on the VAS Satisfaction.